Q. 283.8( 6 Votes )
Prove that (sin θ + sec θ) 2+ (cos θ + cosec θ) 2=(1 + sec θ cosec θ) 2.
L.H.S = (sin θ + sec θ ) 2 + (cos θ + cosec θ ) 2
= [sin θ +(1/cos θ)] 2 + [cos θ + (1/sin θ) ] 2
= 1 + sec 2 θ cosec 2 θ + 2 sec θ cosec θ
= (1 + sec θ cosec θ) 2
Rate this question :
Draw the graph of 2x – 3y = 4. From the graph, find whether x = -1, y = -2 is a solution or not. (Final)NCERT - Mathematics
Prove the following identities :
tan4θ + tan2θ = sec4θ – sec2θKC Sinha - Mathematics
If, then find the values of sin θ and cos θ.KC Sinha - Mathematics
Write the first three terms of the following sequences defined by:
KC Sinha - Mathematics
Express the following as trigonometric ratio of complementary angle of 90o- θ.
(i) tan (90o- θ)
(ii) cos (90o- θ)KC Sinha - Mathematics